Advances in Mud Crab Scylla spp. Fattening: A Critical Synthesis of Production Systems, Nutrition, Water Quality, Health Management and Emerging Technologies - John Yesudhas (Asian Journal of Fisheries and Aquatic Research, 2026)
Mud crab fattening is a short-cycle aquaculture strategy in which lean, recently moulted, low-condition or otherwise under-finished market-sized crabs are held until flesh condition, gonadal development or market grade improves. Its apparent simplicity conceals a tightly coupled production problem: feeding intensity influences water quality; confinement changes aggression and disease transmission; salinity and oxygen modify metabolism and immune competence; and the biological meaning of weight gain depends on moult stage, sex, species and the endpoint chosen. This critical narrative review evaluates advances in fattening of mud crabs of the genus Scylla, with emphasis on production systems, nutrition, water-quality control, health management and emerging technologies. Literature was selected through international and regional scholarly sources for the period 1 January 1998 to 23 June 2026, with earlier evidence retained when conceptually necessary. The strongest direct evidence supports individual compartmentalisation where cannibalism or contact-mediated disease threatens survival, and indicates that controlled recirculating systems can improve environmental stability when salinity, solids and nitrogenous waste are actively managed. Nutritional evidence is less transferable than commonly assumed: protein and amino-acid requirements derived from postlarvae or juveniles cannot be treated as universal targets for short-cycle finishing of market-sized crabs, while direct fattening studies favour stage-specific formulated diets that balance nutrient density with low waste generation. Water-quality studies demonstrate important effects of salinity, temperature, hypoxia and ammonia, but many are acute or juvenile experiments and therefore define biological hazards more reliably than farm operating thresholds. White spot syndrome virus, mud crab reovirus, Hematodinium and pathogenic Vibrio spp. remain important health risks, with evidence increasingly linking disease control to isolation, stress reduction and environmental management rather than treatment alone. Emerging recirculating, habitat-enriched, precision-feeding and digital monitoring approaches are promising, but commercial validation, energy accounting and smallholder affordability remain insufficiently resolved. The field would benefit most from species-verified, stage-specific, farm-scale trials that integrate biological performance, product quality, disease outcomes, resource use and economics.